2015
DOI: 10.1007/s11523-015-0375-8
|View full text |Cite
|
Sign up to set email alerts
|

Vemurafenib pharmacokinetics and its correlation with efficacy and safety in outpatients with advanced BRAF-mutated melanoma

Abstract: Vemurafenib is a BRAF kinase inhibitor approved for first-line treatment of metastatic BRAF (V600) -mutant melanoma. However, data on the pharmacokinetic/pharmacodynamic (PK/PD) relationship are lacking. The aim of this prospective, multicenter study was to explore the PK/PD relationship for vemurafenib in outpatients with advanced BRAF-mutated melanoma. Fifty-nine patients treated with single-agent vemurafenib were prospectively analyzed. Vemurafenib plasma concentration (n = 159) was measured at days 15, 30,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
39
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 28 publications
4
39
1
2
Order By: Relevance
“…Responders had a mean concentration of 56.4 mg/L, while nonresponders had a mean of 38.8 mg/L ( P = 0.013) 87, 88. Moreover, melanoma patients in the lowest exposure quartile (<40.4 mg/L) had a PFS of 1.5 months compared to that of 4.5 months of patients in the higher three quartiles ( P = 0.029) 85. This effect was confirmed in an independent cohort after 12 months of follow‐up with a threshold of 42 mg/L ( P = 0.005) 89…”
Section: Practical Recommendations For Tdm Of Kis In Oncologymentioning
confidence: 71%
See 1 more Smart Citation
“…Responders had a mean concentration of 56.4 mg/L, while nonresponders had a mean of 38.8 mg/L ( P = 0.013) 87, 88. Moreover, melanoma patients in the lowest exposure quartile (<40.4 mg/L) had a PFS of 1.5 months compared to that of 4.5 months of patients in the higher three quartiles ( P = 0.029) 85. This effect was confirmed in an independent cohort after 12 months of follow‐up with a threshold of 42 mg/L ( P = 0.005) 89…”
Section: Practical Recommendations For Tdm Of Kis In Oncologymentioning
confidence: 71%
“…In melanoma patients, vemurafenib concentrations were significantly higher in those patients who developed Grade ≥2 rash compared to those who did not (mean ± standard deviation (SD) of 61.7 ± 25.0 vs. 36.3 ± 17.9 mg/L, P < 0.0001) 85. Another study found an exposure–dependent QTc prolongation for vemurafenib 86.…”
Section: Practical Recommendations For Tdm Of Kis In Oncologymentioning
confidence: 97%
“…Patients with disease progression had lower plasma concentrations compared with patients with stable disease and those who were partial or complete responders. Three independent groups suggested a TDM target concentration of 42 μg/mL . Plasma concentrations exceeding 62 μg/mL have been associated with higher risk for the development of grade ≥ 2 rash .…”
mentioning
confidence: 99%
“…Vemurafenib plasma concentrations have been linked to the risk of disease progression [52][53][54] and/or toxicity (e.g. rash of at least grade 2 severity) [53].…”
Section: Place Of Cobimetinib Plus Vemurafenib In the Management Of Bmentioning
confidence: 99%
“…rash of at least grade 2 severity) [53]. It has been suggested that therapeutic drug monitoring in the early stages of vemurafenib treatment may help identify patients at risk of nonresponse and toxicity [52,53], although more data are needed.…”
Section: Place Of Cobimetinib Plus Vemurafenib In the Management Of Bmentioning
confidence: 99%